Transfer RNA's latest port of call - Santos, Manuel A. S. (2020)
Transfer RNA, or tRNA, has the dubious honor of being a recurring historical figure in molecular biology. Much like the lead character in Woody Allen's movie Zelig, tRNA keeps on turning up in history at the right place at the right time. In this respect the timing of the 23rd installment of the International tRNA Workshop just a few months after the awarding of the Nobel Prize for the structure of the ribosome was particularly fitting. Over 250 scientists gathered from January 28 to February 2, 2010 in the charming town of Aveiro on the Atlantic coast of Portugal to discuss the latest advances in our understanding of the myriad roles of tRNA, which stretch far beyond acting as a simple adaptor in protein synthesis. Topics covered ranged from well-established areas such as the complex post-transcriptional modification of tRNAs, tRNA aminoacylation and protein synthesis, to emerging areas such as mistranslation and human disease, and roles for tRNA outside translation.